2000
DOI: 10.1046/j.1440-1622.2000.01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Wound Infection and Bacteraemia Following Coronary Artery Bypass Surgery

Abstract: These findings suggest that improved diabetic control and pre-operative weight reduction may result in a decrease in the incidence of SWI. But further prospective studies need to be undertaken to examine (i) whether the increased SWI risk in diabetes occurs with both insulin- and non-insulin-requiring diabetes, and whether improved peri-operative diabetes control decreases SWI; and (ii) what degree of obesity confers a risk of SWI and postoperative bacteraemia, and whether pre-operative weight reduction, if a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
3
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 18 publications
(30 reference statements)
3
48
3
6
Order By: Relevance
“…Although previous studies found associations between post-operative SSI and previous operation [7][8][9][10], our study did not demonstrate any correlation. We found that second operation in oral cavity region was not associated with increased post-operative SSI rate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although previous studies found associations between post-operative SSI and previous operation [7][8][9][10], our study did not demonstrate any correlation. We found that second operation in oral cavity region was not associated with increased post-operative SSI rate.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study on risk factors for SSI following coronary artery bypass surgery found previous cardiovascular procedure was an independent predictor of SSI [7]. Omeis et al [8] in their study of post-operative SSI in patients undergoing spinal tumor surgery indicated that previous spinal surgery was significantly associated with increased likelihood of developing post-operative SSI.…”
Section: Introductionmentioning
confidence: 96%
“…But in reality, SV harvest site infection is more common, which increases the morbidity, causes delayed discharge from the hospital, and increases the hospital costs. [7][8][9] The causes of GSVHSI are multifactorial. Prevention is better than cure.…”
Section: Risk Factors Associated With Gsvhsimentioning
confidence: 99%
“…Coagulase-negative staphylococci and Staphylococcus aureus were the leading causes of SSIs following cardiovascular surgery, especially in the sternal area as in previous studies. 4,6 Methicillin resistance among staphylococci was high in our study. Methicillin-resistant staphylococci were all susceptible to vancomycin and teicoplanin, and trimethoprim-sulfamethoxazole susceptibility was greater than 90%.…”
mentioning
confidence: 46%